A HISTOLOGICAL STUDY OF BROILER CHICKENS COLON GIVEN BUTYRIC ACID SUPPLEMENTS - Hidayati, Zumara Mufida; Berata, I Ketut; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2019)
This study aims to determine the differences dosage and duration of butyric acid supplements on the layer thickness of colon broiler chicken. The sample consisted of 24 broiler chickens. This study used a Completely Randomized Design 3x4 factorial pattern that consisted of 3 factors of supplement dosage (0; 0.5; and 1 g supplement/ kg of feed) and duration of administration (1,2,3 and 4 weeks). Samples were divided into 3 groups: control group (P1), the group with butyric acid supplementation 0.5 (P2), and group with 1 g supplement/kg of feed (P3). Every week, two broiler chickens from each group were necropsied and the colonic tissue was taken for histologically preparations using HE staining. The changes observed were on the thickness of mucosal, submucosal, muscular, and serous’s layer and then examined under a microscope and then calculated using ZEN applications. Data were analyzed using Analysis of Variance and followed by Duncan test if there is a significant difference. The results showed the difference in the dose of butyric acid did not affect the thickness of the colon layer but it affects the colon histological changes. The difference in the duration of butyric acid administration affects the thickness of the tunica mucosa, submucosa, muscular, and serosa. It is concluded that the administration of butyric acid between doses 0; 0,5; and 1 g/kg chicken food did not affect for the thickness of the mucosal, submucosal, muscular, and serous’s layer, but it affected the presence of the colon histological changes. Differences in the duration of butyric acid’s administration at week 1,2,3,4 affects the thickness of the mucosal, submucosal, muscular, and serosal’s layer of broiler chicken.